The evolution of the earnings distribution in a volatile economy: Evidence from Argentina - Andres Blanco; Bernardo Diaz de Astarloa; Andres Drenik; Christian Moser; Danilo Trupkin (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
This paper studies earnings inequality and dynamics in Argentina between 1996 and 2015. Following the 2001-2002 crisis, the Argentine economy transitioned from a low- to a highinflation regime. At the same time, the number of collective bargaining agreements increased, and minimum wage adjustments became more frequent. We document that this macroeconomic transition was associated with a persistent decrease in the dispersion of real earnings and cyclical movements in higher-order moments of the distribution of earnings innovations. To understand this transition at the micro level, we estimate processes of regular wage adjustments within job spells. As the Argentine economy transitioned from low to high inflation, the monthly frequency of regular wage adjustments almost doubled, while the distribution of changes in regular wages morphed from having a mode close to zero and being positively skewed to having a positive mode and being more symmetric.
Keywords: D31; E24; E31; J31; 330; Income Inequality; Income Volatility; Income Mobility; Wage Rigidity; Inflation